Enrichment of ewe cheese with Laminaceae seed oil as a source of omega-3 - Muñoz-Tébar N.; de la Vara J.A.; Molina A.; Carmona M.; Berruga M.I. (Innovation for sustainability in sheep and goats, 2019)
In this study we evaluated the viability of using oil extracted from Laminaceae seeds with a hydraulic press at room temperature as a source of omega-3 enrichment for ewe cheeses. Two concentrations (1.5 and 2.5%; vol/vol) of seed oil prepared as emulsions stabilized with calcium caseinate were assayed in pressed sheep`s milk cheeses, and their physicochemical (fat, protein, dry matter and fattty acids), microbiological (total bacteria, lactic acid bacteria, enterobacteria, yeast and moulds) and organoleptic parameters were evaluated during 32 days of ripening. Sheep’s milk coagulation parameters during cheese elaboration were not affected by the incorporation of the oil emulsion. The fortification with the emulsion had a positive impact on the cheese yield, obtaining 2% more in the cheeses containing 2.5% of vegetal oil. Similar results were observed in the fat, dry matter and omega-3 content, which increased proportionally to oil concentration. Moreover, total bacteria and lactic acid bacteria were not inhibited in the cheeses containing the highest oil concentration, confirming the hypothesis that oil addition would not interfere to the normal ripening process. We did not detect the presence of yeast, moulds or enterobacteria in any of the cheeses during ripening. Regarding the sensory analysis, the test “difference from control” showed that no significant differences were observed between the control and the enriched cheeses according to a semi-trained panel of judges.
2. Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2017/10/03-05, Vitoria-Gasteiz (Spain)